2019
DOI: 10.1155/2019/7416419
|View full text |Cite
|
Sign up to set email alerts
|

Young Coconut Juice Reduces Some Histopathological Changes Associated with Alzheimer’s Disease through the Modulation of Estrogen Receptors in Orchidectomized Rat Brains

Abstract: Propose. This study aimed to evaluate the protective role of young coconut juice (YCJ) against the pathological changes in Alzheimer's disease (AD) in orchidectomized (orx) rats. Methods and Results. Animals were divided into 7 groups including: baseline normal control group, sham control, orx rat group, orx rat group injected with 2.5 μg/kg b.w. estradiol benzoate (EB) 3 days a week for 10 weeks, and the orx rat groups treated orally with 10, 20, and 40 ml/kg b.w. of YCJ for 10 weeks. At the end of treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…YCJ was found to prevent osteoporosis (Yusuh et al, 2010;Suwanpal et al, 2011), preserve cells involved in motility of the gastrointestinal tract (Radenahmad et al, 2014), accelerate wound healing, and improve skin complexion (Radenahmad et al, 2012). It was also found that YCJ at a dose of40 ml/kgb.w./day was the best to reduce AD pathologies in ovariectomized rats within 10-weeks (Balit et al, 2019). However, a high dose of YCJ supplement had caused unfavorable side effects, such as glycogen deposition in the liver.…”
Section: Effect Of Hormone In Reducing the Chance Of Admentioning
confidence: 99%
“…YCJ was found to prevent osteoporosis (Yusuh et al, 2010;Suwanpal et al, 2011), preserve cells involved in motility of the gastrointestinal tract (Radenahmad et al, 2014), accelerate wound healing, and improve skin complexion (Radenahmad et al, 2012). It was also found that YCJ at a dose of40 ml/kgb.w./day was the best to reduce AD pathologies in ovariectomized rats within 10-weeks (Balit et al, 2019). However, a high dose of YCJ supplement had caused unfavorable side effects, such as glycogen deposition in the liver.…”
Section: Effect Of Hormone In Reducing the Chance Of Admentioning
confidence: 99%